Enhancing productivity, soil health, and reducing global warming potential through cropping systems diversification and conservation agriculture in India's Western Indo-Gangetic Plains - Gora, M.K.; Jat, H.S.; Ladha, J.K.; Choudhary. Madhu; Sharma, Prabodh Chandra; Yadav, Arvind K.; Singh, Love K.; Sapkota, Tek Bahadur; Singh, Yadvinder; Prajapat, Kailash; Yadav, Rajender Kumar; Jat, Mangi L.; et al. (TAFSSA, 2023)
Evidence suggests that intensive tillage, crop residue removal/burning, and frequent soil wetting-drying cycles in rice-wheat rotations have led to declining soil organic matter and increased greenhouse gas emissions (GHG), and a consequent deterioration of soil quality (Jat et al., 2023). Conservation agriculture (CA) practices, which include reduced or zero tillage combined with residue mulching, crop diversification (e.g., substituting rice with upland crops), and integrating legumes into intensive cereal-based crop rotations, have been recognized for their ability to enhance soil health, increase crop yields, and reduce GHG emissions (Jat et al., 2023). However, there is still limited information available regarding the assessment of different CA scenarios and their impact on soil health, GHG mitigation, and carbon balance in cereal-based rotations.